Elevated oxidative damage is correlated with reduced fitness in interpopulation hybrids of a marine copepod - Barreto, Felipe S. (The Royal Society, 2013)
Aerobic energy production occurs via the oxidative phosphorylation pathway (OXPHOS), which is critically dependent on interactions between the 13 mitochondrial DNA (mtDNA)-encoded and approximately 70 nuclear-encoded protein subunits. Disruptive mutations in any component of OXPHOS can result in impaired ATP production and exacerbated oxidative stress; in mammalian systems, such mutations are associated with ageing as well as numerous diseases. Recent studies have suggested that oxidative stress plays a role in fitness trade-offs in life-history evolution and functional ecology. Here, we show that outcrossing between populations with divergent mtDNA can exacerbate cellular oxidative stress in hybrid offspring. In the copepod Tigriopus californicus, we found that hybrids that showed evidence of fitness breakdown (low fecundity) also exhibited elevated levels of oxidative damage to DNA, whereas those with no clear breakdown did not show significantly elevated damage. The extent of oxidative stress in hybrids appears to be dependent on the degree of genetic divergence between their respective parental populations, but this pattern requires further testing using multiple crosses at different levels of divergence. Given previous evidence in T. californicus that hybridization disrupts nuclear/mitochondrial interactions and reduces hybrid fitness, our results suggest that such negative intergenomic epistasis may also increase the production of damaging cellular oxidants; consequently, mtDNA evolution may play a significant role in generating postzygotic isolating barriers among diverging populations.